Síntese de Bio-MOF a base de aminoácidos e metais atóxicos para potenciais aplicações farmacológicas - Zanotelli, Natália Cristina (2022)
Through a simple, cheap and sustainable methodology, a new synthetic route was designed for the synthesis of MOF structures with copper, cobalt and zinc metals and using amino acid glutamic acid as a ligand. The success of the green synthesis was confirmed by the techniques of X-ray diffractometry, infrared spectroscopy and thermal analysis, obtaining the same profile as in the literature. Thus, with the promising materials obtained by an environmentally friendly route, it was proposed to replace the water ligand with a drug molecule. Although with the drug isoniazid the reaction did not maintain the structure of a MOF, with the two isoniazid derivatives the results obtained show the formation of a different compound and crystalline. However, the highlight is the new structure synthesized with the drug norfloxacin, a structure characterized by single crystal diffraction, X-ray diffractometry, thermal analysis and infrared spectroscopy. The new coordination polymer presents the cobalt metallic center coordinated to four drug ligands, forming a two-dimensional structure, which, when interacting with each other, give rise to a three-dimensional and porous structure, opening a range of possibilities for the material, in addition to an alternative antimicrobial resistance. Potential pharmacological applications are also possible for all materials since the preliminary tests of antimicrobial activity carried out with the bacteria E. coli and P. aeruginosa showed a superior potential to the drug used as a control, in addition to the cytotoxicity test using the microcrustacean Artemia salina which shows the safety of materials in small doses.